2013
DOI: 10.3892/ijo.2013.2163
|View full text |Cite
|
Sign up to set email alerts
|

A novel hydroxamic acid derivative, MHY218, induces apoptosis and cell cycle arrest through downregulation of NF-κB in HCT116 human colon cancer cells

Abstract: Colorectal cancer (CRC) is one of the most common malignant diseases and frequent cause of cancer deaths in the world. In spite of the significant advances in conventional therapeutic approaches to CRC, most patients ultimately die of their disease. There is a need to develop novel preventive approaches for this malignancy. This study was carried out to investigate the anticancer effect of MHY218, a hydroxamic acid derivative, in HCT116 human colon cancer cells. Treatment of cells with MHY218 resulted in growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
6
11
0
Order By: Relevance
“…It was found to cause apoptosis in SKOV-3 ovarian cancer cells. This histone deacetylase (HDAC) inhibitor exhibits growth inhibitory effects in several tumor cell lines, including ovarian, breast, and colon cancer cells (10)(11)(12). Two studies in animals have shown that MHY218 has antineoplastic activities against tamoxifen-resistant breast cancer and ovarian cancer (10,11).…”
Section: Mhy218-induced Apoptotic Cell Death Is Enhanced By the Inhibmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found to cause apoptosis in SKOV-3 ovarian cancer cells. This histone deacetylase (HDAC) inhibitor exhibits growth inhibitory effects in several tumor cell lines, including ovarian, breast, and colon cancer cells (10)(11)(12). Two studies in animals have shown that MHY218 has antineoplastic activities against tamoxifen-resistant breast cancer and ovarian cancer (10,11).…”
Section: Mhy218-induced Apoptotic Cell Death Is Enhanced By the Inhibmentioning
confidence: 99%
“…The anticancer mechanisms of MHY218 are still under investigation, and few studies have reported its effects on cell death. It has been shown to induce the pro-apoptotic Bax protein, inhibit the anti-apoptotic Bcl-2 protein (10)(11)(12), and suppress the nuclear translocation of nuclear factor-κB (NF-κB) (12). Thus, modulations of the NF-κB-regulated genes such as cyclooxygenase-2, matrix metalloproteinase-9, 5-lipoxygenase (12), and HDACs (10,11) have been implicated in MHY218-induced apoptotic cell death.…”
Section: Mhy218-induced Apoptotic Cell Death Is Enhanced By the Inhibmentioning
confidence: 99%
See 2 more Smart Citations
“…Colon cancer is one of the most common solid tumors and frequent cause of cancer-related mortality worldwide (1,2). Despite significant progress in conventional therapeutic approaches to colon cancer, most patients eventually succumb to their disease.…”
Section: Introductionmentioning
confidence: 99%